تفعيل الاستثمار الأجنبي المباشر في الجزائر باتجاه التنمية المستدامة - خضور رسلان; شبانة ناديا (Latakia University Journal - Economic and Legal Sciences Series, 2017)
أمام الاهتمام المتزايد والسباق بين مختلف الدول نحو الاستثمار الأجنبي المباشر لاسيما بعد الأزمة المالية والاقتصادية العالمية والتطورات السياسية الأخيرة في المنطقة العربية، وأزمة منطقة اليورو والانكماش الذي عرفته الأسواق العالمية للاستثمار، هذا إلى جانب التطورات الحديثة التي طرأت على اتجاهات رؤوس الأموال الأجنبية، تسعى كل الدول خاصة النامية منها جاهدة إلى توفير الظروف المواتية لاجتذاب الاستثمار الأجنبي المباشر. والجزائر كغيرها من الدول النامية ليست بمنأى عن هذه التحولات مما يستدعي؛ انتهاج سياسات وإصلاحات تهيئ بيئتها الاقتصادية المناسبة وإقرار سياسة الباب المفتوح أمام الاستثمار الأجنبي للتوائم وهذه التطورات، لأجل الاستفادة من مزاياها ولتعزيز قدراتها التنافسية في عالم مفتوح أمام التجارة وأمام الاستثمارات الأجنبية والدخول في دائرة النمو الاقتصادي وتحقيق التنمية المستدامة عموما.تهدف هذه الدراسة إلى التعرفعلى الإجراءات التي تسعى الجزائر من خلالها إلى تفعيل الاستثمار الأجنبي المباشر باتجاه التنمية المستدامة باعتبارها مطلباً أساسياً لتحقيق العدالة والإنصاف في توزيع مكاسب التنمية والثروات بين الأجيال المختلفة. Given the growing interest and the race between countries to foreign direct investment, especially after the financial policies and recent developments and global economic crisis in the Arab region, and the crisis in the euro zone and the recession in the global investment market, with the moderns developments in foreign investment trends, all countries and especially developing countries seek to provide favorable conditions for attracting foreign direct investment, and Algeria, like other developing countries, are not immune to these changes, which calls for the adoption of policies and reforms that create the appropriate economic environment and adopt a policy of open door to foreign investment so that it matches these developments in order to benefit from its advantages and strengthen their competitiveness in an open world trade and foreign investment and at the end engage in the circle of economic growth and achieve sustainable development in general. This paper aims to find out the measures by which the Algeria seeks to enable foreign direct investment towards sustainability, as sustainable development is a prerequisite for the realization of justice and equity in the distribution of development gains and wealth between generations.